Current issues of banking approaches for assessing the credit risk of a corporate borrower in conditions of instability - Yuzvovich, Larisa; Novikova, Natalia; Kotova, Olga; Popova, Natalia; Vorotilova, Olga (Nexo Revista Científica, 2022)
The article is devoted to the issue of assessing the credit risk of a corporate borrower of a bank in the conditions of the coronavirus pandemic and its consequences. The situation in the banking sector in the current conditions has been outlined, the directions of the regulator for improving the banking sector within the framework of a risk-oriented approach have been presented. The necessity of modernization of methods for calculating credit risk based on the model of expected losses, taking into account the superposition of the factor of cyclical fluctuations of economic systems, has been revealed.